2008
DOI: 10.1007/s00405-008-0647-3
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular decompression of cochleovestibular nerve

Abstract: The role of microvascular decompression (MVD) in the management of trigeminal neuralgia, hemifacial spasms and glossopharyngeal neuralgia is well-established. However, controversy persisted as to the use of MVD in cochleovestibular neurovascular compression syndrome. This report provides a review of all the published studies on MVD of the eighth (8th) nerve in alleviating cochleovestibular symptoms and presents three additional patients who underwent MVD of the eighth nerve for tinnitus or vertigo. Nineteen st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 58 publications
1
34
0
2
Order By: Relevance
“…T2-VISTA imaging of the IAC and CPA was performed with the following parameters: FOV, 160 ϫ 160 mm 2 …”
Section: Mr Imaging Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…T2-VISTA imaging of the IAC and CPA was performed with the following parameters: FOV, 160 ϫ 160 mm 2 …”
Section: Mr Imaging Protocolmentioning
confidence: 99%
“…[1][2][3][4] Among these clinical symptoms, typewriter tinnitus, which was first described by a pediatric cardiologist as "ear-clicking tinnitus responding to carbamazepine," 5 is characterized by paroxysmal attacks. It is either spontaneous or precipitated by positioning or sounds and occurs with staccato sounds described as "Morse code," "machine gun," "coins in a can," "crackling," or "typewriter" sounds.…”
mentioning
confidence: 99%
“…The timing of surgery for CNVC with chief complaint of tinnitus should be limited as some reports. Significant improvements in the intensity of tinnitus were achieved in some patients with symptoms for less than 2 years, as described by Sakaki et al [5], Bookes [9], and Yap et al [13], and in those with symptoms for between 2 and 4 years, as found by Sakaki et al [5] and Ryu et al [10]. Significant improvements [10,14] in tinnitus has been reported even in patients persisting 4-6 years.…”
Section: Discussionmentioning
confidence: 70%
“…Several diagnostic processes [4,[7][8]12,13] related to the features of CNVC have been reported: recurrent vertigo, intractable tinnitus, and the progressive hearing loss. Neuro-otological examinations involving vestibular testing and an ABR evaluation [2,8] are very important.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation